The coverage of hepatitis B birth dose vaccination in Nigeria: Does the place of delivery matter?. (27th August 2021) - Olakunde, Babayemi O; Adeyinka, Daniel A; Olakunde, Olubunmi A; Ogundipe, Temitayo; Oladunni, Filani; Ezeanolue, Echezona E
Abstract: Background: Hepatitis B birth dose (HepB-BD) vaccination coverage remains suboptimal in Nigeria. While evidence suggests that institutional delivery is associated with the uptake of HepB-BD vaccine, little is known about how the uptake differs by facility ownership (public or private). This study examined the HepB-BD vaccination coverage by place of delivery in Nigeria. Methods: This study is a secondary analysis of data on 6143 children aged 12–23 mo obtained from the 2018 Nigeria Demographic and Health Survey. We assessed the association between HepB-BD vaccination and the place of delivery using logistic regression models. Results: About 53% of the children received the HepB-BD vaccine. Approximately 77, 83 and 33% of those delivered at a public health facility, private health facility and at home received the HepB-BD vaccine, respectively. After controlling for child- and maternal-level factors, the odds of receiving HepB-BD vaccine were significantly lower in children delivered at a private health facility (adjusted OR [aOR]=0.77, 95% CI 0.59 to 0.99) or at home (aOR=0.48, 95% CI 0.36 to 0.63). Wealth index and region of residence were significantly associated with the receipt of HepB-BD vaccination in all three places of delivery. Conclusions: Children are less likely to receive the HepB-BD vaccine if they are delivered at a private health facility or at home. There is a need for private health sector engagement for immunization service delivery and innovative community-based interventions to reach the children delivered at home.